The application of transcritical CO2 system with ejector in large cold store - 赖坤; 田健 (Zhileng xuebao)
As a natural refrigerant, CO2 has advantages such as environmental friendliness, safety and high volume cooling capacity. Therefore, the application of transcritical CO2 systems in large cold storages will improve energy efficiency, reduce carbon emissions and promote environmental protection. The performance and energy consumption characteristics of different refrigeration systems were compared through a comprehensive annual hourly energy consumption analysis, based on different temperature range cold storage demand and various climate conditions. The results show that the transcritical CO2 system integrated with specifically optimized ejector can achieve energy savings of 7.9%, 10.1% and 10.5% in for low temperature (-32°C), medium temperature (-8°C) and high temperature (0°C) cold storages compared with the traditional R507 system; the energy saving of R717 system is 8.1%, 2.7% and 7.2% compared with the R507 system, respectively. The energy saving of the R717 system is slightly higher than that of the CO2 system in the low temperature cold storage, but the advantages of the CO2 system are more obvious in the medium and high temperature cold storage. Considering the influence of different climate zones, the energy saving of the CO2 system can reach 9.3% in the cold climate zone, better than the R717 system; while in the hot climate zone, its energy saving drops to 2.8%, slightly lower than that of R717. With appropriate selection of temperature range and climate zone, the overall operation efficiency and energy saving performance of the transcritical CO2 system can be better than the R717 system. This paper conducts a comprehensive analysis on the energy consumption distribution characteristic of the CO2 system, and points out its applicability in different application scenarios, providing important references for the promotion and application of the system. In conclusion, the application of transcritical CO2 refrigeration system with ejector in large cold storage, can significantly reduce both direct and indirect carbon emissions, decrease overall energy consumption, will play great role in achieving dual carbon goals.